The Influence of Christian on Modern Chinese Morals Viewed from the Evolution of the Name and Contents of Temperance Department - MA Guangxia, (Journal of Research for Christianity in China (JRCC), 2025)
American Methodist Episcopal Church, South, which entered the field of China in 1848 and was united into Methodist Church in 1939, has built up huge church enterprises and multifunctional Christian community with modern and local features in the process of complicated and dynamic communication with local society, though it is not a big mission organization in terms of its missionaries and the financial allocation. The reasons are as follows: the development of modern Chinese society, two local factors from the traditional society in the south of Yangtze River and new Shanghai providing more local force between the worker and the finiance, and the important role played by the standard management system of it. As an example, in order to restrain church members’ behavior, Methodist Episcopal Church South not only has a temperance department which was in the charge of an appointed person, but also has a special report about it at the Annual Conference. From the late Qing Dynasty to the Repbulic of China, this department has been envolving, so it has a certain impact on the modernization of Chinese traditional moral.